KETERAMPILAN AKRUPAMA SISWA KELAS VIII SMP NEGERI 4 TAKALAR: Akrupama Skills of Grade Viii Students of Smp Negeri 4 Takalar - Irwan, Adityana Purnama; Daeng, Kembong; M, Asia (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the storytelling skills of eighth-grade students at SMP Negeri 4 Takalar. The research method used is a descriptive method with a quantitative approach. This descriptive method involves collecting data to test hypotheses or answer questions about people's opinions on an issue or topic. Quantitative research emphasises analysis of numerical data processed using statistical methods. With the quantitative method, the significance of the relationship between variables will be obtained. The reason the researcher chose this type of research is because it is very effective for researching students' storytelling skills. The results of the study on the storytelling skills of skilled students show that the recapitulation of the aspect score is 71.87, which is in the range of 56-75. This falls under the category of fairly skilled. From several assessment aspects, namely: (a) language usage skills, which include the proper and correct use of the Makassar language and communicative or easily understood by the audience (children), (b) vocal processing skills (articulation, tempo, and appropriate intonation), (c) mastery of the material, (d) expression/interpretation skills, (e) creativity, including costumes, props, and stage presence. Thus, it can be concluded that the students' storytelling skills are categorised as fairly skilled because, out of the 32 samples, 71.87% of the students obtained scores in the 56-75 range, which is the highest skill level.